Technologies to obtain peanut seeds with superior quality: from field to gene - Oliveira, Gustavo Roberto Fonseca de [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The quality of peanut seeds is essential for optimized germination, storage and the rapid, uniform establishment of seedling in the field (vigor), making it crucial for agriculture. This study explores innovative methods associated with the physiological quality of peanut seeds at different development stages and in the post-harvest phase, with approaches focusing on maturation, chemical composition, spectroscopy techniques, and gene expression. In Chapter 1, the effectiveness of combining multispectral imaging with artificial intelligence was investigates to autonomously and non-destructively identify seedlots with superior vigor. New markers of seed and seedling performance, such as anthocyanin, were identified, opening new perspectives for seed vigor analysis. In Chapter 2, the challenge of determining the ideal harvest time for peanut seeds in the field was addressed. Focusing on the maturation and late maturation phases, this research proposes a novel maturation scale for peanut in tropical agriculture, providing practical guidelines for harvesting peanut seeds with superior germination, desiccation tolerance, vigor, longevity, and health (seed quality attributes). In Chapter 3, the chemical composition of seeds at different development stages was explored, examining whether non-destructive techniques commonly used in other sectors (e.g., LIBS in the mining industry) can identify chemical patterns associated with mature seeds. Techniques such as Nuclear Magnetic Resonance, Laser-Induced Breakdown Spectroscopy (LIBS), and X-ray Fluorescence were effective in identifying seeds with superior vigor through the digital dynamics of oil and minerals. Finally, in Chapter 4, the expression of genes associated with flavonoid biosynthesis, specifically the anthocyanin pathway, was investigated, along with their possible involvement in the acquisition of the seed quality attributes. The secondary metabolism of peanuts was explored during seed maturation phases, revealing contributions to the species' biology and biotechnological applications in Brazilian agriculture. Together, these four studies provide a comprehensive understanding of the physiological, chemical, spectral and molecular aspects of peanut seeds, as well as valuable insights for the technological advancement of this crop production system in Brazil and worldwide.

A qualidade das sementes de amendoim é essencial para uma germinação otimizada, armazenamento e estabelecimento rápido e uniforme das plântulas no campo (vigor), sendo crucial para a agricultura. Este estudo explora métodos inovadores associados à qualidade fisiológica das sementes de amendoim em diferentes estádios de desenvolvimento e na pós-colheita, com abordagens sobre a maturação, composição química, técnicas de espectroscopia e expressão gênica. No Capítulo 1, a eficácia da combinação de imagens multiespectrais com inteligência artificial foi investigada para identificar de forma autônoma e não destrutiva lotes de sementes com qualidade superior. Marcadores inéditos do desempenho de sementes e plântulas, como a antocianina, foram encontrados abrindo novas perspectivas para a análise do vigor de sementes. No Capítulo 2, foi abordado o desafio de determinar o momento ideal para a colheita de sementes de amendoim no campo. Focando nas fases de maturação e maturação tardia, esta pesquisa propõe uma escala de maturação inédita para o amendoim na agricultura tropical, fornecendo diretrizes práticas para a colheita de sementes com germinação, tolerância à dessecação, vigor, longevidade e sanidade superiores (atributos da qualidade). No Capítulo 3, explorou-se a composição química das sementes nos diferentes estádios de desenvolvimento, examinando se técnicas não destrutivas comuns em outros setores (ex: LIBS na indústria de mineração) podem identificar padrões químicos associados às sementes de amendoim maduras. Técnicas como Ressonância Magnética Nuclear, Espectroscopia de Ruptura Induzida por Laser (LIBS) e Fluorescência de Raios X foram eficazes para identificar sementes com vigor superior por meio da dinâmica digital de óleo e minerais. Por fim, no Capítulo 4, foi investigado a expressão dos genes associados a biossíntese de flavonoides, rota das antocianinas, e o possível envolvimento deles com a aquisição dos componentes de qualidade das sementes. O metabolismo secundário do amendoim foi explorado durante as fases de maturação, revelando contribuições à biologia de sementes da espécie e aplicações biotecnológicas na agricultura brasileira. Juntos, esses quatro estudos fornecem uma compreensão abrangente sobre os aspectos fisiológico, químico, espectral e molecular das sementes de amendoim além de valiosos insights para o progresso tecnológico do sistema produtivo da cultura no Brasil e no mundo.
Tecnologias para obter sementes de amendoim com qualidade superior: do campo ao gene
Keywords: Amendoim; Imagens multispectrais; Antocianina; Sementes; Sementes; Expressão gênica